Clinical Efficacy and Safety of Xinmailong Injection for the Treatment of Chronic Heart Failure: A Meta-Analysis - Xiaohua Lu; Xiaohua Lu; Lu Zhang; Lu Zhang; Jiabo Wang; Honghong Liu; Haotian Li; Houqin Zhou; Houqin Zhou; Rongrong Wu; Yuxue Yang; Yuxue Yang; et al. (Frontiers Media S.A., 2018)
Background: Chronic heart failure (CHF) is one of the most stubborn cardiovascular disease. Xinmailong (XML), a bioactive fraction extracted from Periplaneta americana L., has been commonly used for CHF treatment in China. However, there is few comprehensive evaluation for the clinical efficacy and safety of XML for CHF.Objectives: We aimed to evaluate the beneficial and adverse effects of Xinmailong Injection (XMLI) on CHF treatment with the use of meta-analysis.Methods: In accordance with the Cochrane Handbook and transparent reporting of systematic reviews and meta-analysis protocol (CRD42018087091), seven English and Chinese electronic databases, including PubMed, EMBASE, Cochrane Library, Chinese National Knowledge Infrastructure (CNKI), Wanfang database, VIP medicine information system and China Biomedical Literature Database (CBM), were searched to retrieve potential randomized controlled trials (RCTs) before November 2017. The eligible trials were evaluated for methodological quality. The main outcome measures were analyzed with RevMan 5.3 software.Results: 26 RCTs involving 3447 participants were subjected to meta-analysis. The total effective rate was improved by XMLI plus conventional therapy (OR 3.10, 95% CI 2.47-3.90, P < 0.00001). When compared to the conventional treatment alone, the combination of XMLI and conventional treatment increased left ventricular ejection fraction (LVEF, MD 4.93, 95% CI 3.96-5.89, P < 0.00001) and 6-min walking distance (6-MWD, MD 46.76, 95% CI 32.51 to 61.01, P < 0.00001), and decreased left ventricular end-diastolic diameter (LVEDD, MD −4.73, 95% CI−5.64 to−3.83, P < 0.00001), serum brain natriuretic peptide (BNP, MD −149.59, 95% CI −211.31 to −87.88, P < 0.00001) and N-terminal pro-brain natriuretic peptide (NT-proBNP, MD −322.35, 95% CI −517.87 to −126.83, P = 0.001). However, the frequency and severity of adverse effects was similar between these two different medications. Poor methodological quality and the limitations also existed in this study.Conclusions: The combinational use of XMLI on conventional treatment may exert better therapeutic effects on improving cardiac function in CHF patients, indicating that XMLI was suggested to be considered during the conventional treatment of CHF. High-quality and large scale RCTs are still required to confirm the impacts of XMLI.